Serum fetuin-A levels in subjects with and without choroid plexus calcification - Ceylan, Mustafa; Bayraktutan, Omer Faruk; Atis, Omer; Yalcin, Ahmet; Kotan, Dilcan; Yilmaz, Tulay (Neuroscience letters, 2015)
•Fetuin-A plays important roles in inflammation and inhibition of mineralization.•Fetuin-A is linked with various central nervous system pathologies.•Subjects with choroid plexus calcification have lower serum levels of fetuin-A. Choroid plexus is an intraventricular plexus of tissue which is responsible for secretion of cerebrospinal fluid. Calcification of choroid plexus is found to be associated with age and gender. One of novel and popular glycoprotein that involves in inhibition of mineralization is human fetuin-A. In our study, we investigated plasma levels of fetuin-A in subjects with and without choroid plexus calcification. For this purpose, 41 subjects with choroid plexus calcification and 41 age and gender matched subjects with normal appearing choroid plexus were recruited. Calcified and normal choroid plexus tissue identified on computed tomography images. Overnight fasting venous blood samples were collected to measure serum fetuin-A levels using a human fetuin-A enzyme-linked immunosorbent assay kit. Statistically significant difference concerning the median concentration of fetuin-A was found between subjects with and without choroid plexus calcification (p: 0.040). Significance was also present between male subgroups (p: 0.017) and 18–27 years age subgroups (p: 0.025). Our results suggest that fetuin-A has an potent role in calcification process of choroid plexus.